Production of a cyanobacterium-based biodiesel by the heterogeneous biocatalyst of SBA-15@oleate@lipase. (1st November 2020) - Imanparast, Somaye; Faramarzi, Mohammad Ali; Hamedi, Javad
Graphical abstract: Highlights: SBA-15 was doped by oleic acid as highly selective and efficient hydrophobic support. SBA-15@oleate@lipase was developed based on interfacial activation mechanism. The maximum immobilization yield (80%) was attained at 200 µg ml −1 of the protein. Biodiesel production with 85%±3.2 conversion was performed by the heterogeneous biocatalyst. The heterogeneous biocatalyst showed a high capability to produce methyl palmitoleate. Abstract: Rising world demand coupled with diminishing supply of fossil fuels and petroleum products have led to look for alternative renewable and clean fuels such as biodiesel. The production of biodiesel can be facilitated with suitable biocatalysts. In the present study, a mesoporous silica of SBA-15 modified with oleic acid and a solvent tolerant lipase from Actinomadura sediminis (SBA-15@oleate@lipase) was designed as the heterogeneous biocatalyst with maximum activity by a protein loading of 32.0 mg per gram of the support. The maximum immobilization efficiency (68%) and yield (80%) were also obtained at 200 µg ml −1 of the protein with reaction time of 60 min. The enzymatic trans-esterification reaction was catalyzed for converting oil of the cyanobacterium Synechococcus elongatus into biodiesel with an 85% ± 3.2 yield under optimized conditions. The designed heterogeneous biocatalyst revealed a high efficiency towards palmitoleic acid (C16:1) in the microalgal oil that is one of the best fatty acids to produce a high-quality biodiesel. This work also highlights the simultaneous combination of purification and immobilization of the bacterial lipase by interfacial activation mechanism, to the synthesis of a solid biocatalyst for production of a cyanobacterium-based biodiesel.